Equilibrium with default-dependent credit constraints - Emma Moreno-García; Juan Pablo Torres-Martínez (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2007)
We state an infinite horizon sequential markets model with real assets in positive net supply and subject to credit risk. By introducing default-dependent borrowing constraints, we show the existence of equilibrium.
Keywords: 330; Equilibrium; Infinite horizon incomplete markets; Infinite-lived real assets.